2006
DOI: 10.1007/s11274-006-9321-3
|View full text |Cite
|
Sign up to set email alerts
|

Elicitor-enhanced syringin production in suspension cultures of Saussurea medusa

Abstract: Syringin production and related secondary metabolism enzyme activities in suspension cultures of Saussurea medusa treated with different elicitors (yeast extract, chitosan and Ag + ) were investigated. All elicitors enhanced syringin production, and the optimal feeding protocol was the combined addition of 1.5%

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 19 publications
(18 reference statements)
1
17
0
Order By: Relevance
“…A similar observation was obtained in suspension cultures of Saussurea medusa Maxim and Linum album Boiss (Xu et al, 2007;Shams-Ardakani et al, 2005). In view of the positive effects of manipulation of the components of culture medium, the growth and flavonolignan production of S. marianum cell suspension were tested using different concentrations of KNO 3 , KH 2 PO 4 , iron, and calcium.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…A similar observation was obtained in suspension cultures of Saussurea medusa Maxim and Linum album Boiss (Xu et al, 2007;Shams-Ardakani et al, 2005). In view of the positive effects of manipulation of the components of culture medium, the growth and flavonolignan production of S. marianum cell suspension were tested using different concentrations of KNO 3 , KH 2 PO 4 , iron, and calcium.…”
Section: Discussionsupporting
confidence: 72%
“…The mechanisms of elicitation of secondary metabolite production by cell suspension cultures are not fully understood. However, many studies suggest that an elicitor signal is perceived by a receptor on the surface of the plasma membrane and initiates a signal transduction network, which regulates the expression of biosynthesis genes involved in plant secondary metabolism and further key enzymes that catalyze the biosynthesis of the target secondary metabolites (Xu et al, 2007;Zhao et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that the elicitation effects might be due to other components, still not being identified (Ertola & Hours 1998). In many species it has been proven to stimulate or decrease different secondary metabolites, such as syringin, valeportriates, podophyllotoxin and silymarin (Kittipongpatana et al 2002;Shams-Ardakani et al 2005;Xu et al 2007;Hasanloo et al 2009). Our current work revealed that YE is a stimulating factor for TA production in A. acutangulus plant, which gradually boosted the contents of hyoscyamine and scopolamine in the root and stem in the range of 96 h treatment, the same as the key genes of TA biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Lots of experiments have demonstrated that MJ was able to stimulate the production of several compounds in many species (Ignatov et al 1996;Rijhwani & Shaks 1998;Dong & Zhong 2002;Wang & Zhong 2002;Vasconsuelo & Boland 2007). Yeast extract (YE), a kind of polysaccharide, was also been reported to have the ability to regulate increase or decrease different secondary metabolites in many species, such as syringin, valeportriates, podophyllotoxin and silymarin (Kittipongpatana et al 2002;Shams-Ardakani et al 2005;Xu et al 2007;Hasanloo et al 2009). Abscisic acid (ABA), also called resistant inducer element, is a key element which can balance the plant endogenous hormones and is relevant to growth-active substances.…”
Section: Introductionmentioning
confidence: 99%